2017
DOI: 10.1016/j.dsr2.2017.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Energy transfer in the Congo deep-sea fan: From terrestrially-derived organic matter to chemosynthetic food webs

Abstract: Large amounts of recent terrestrial organic matter (OM) from the African continent are delivered to the abyssal plain by turbidity currents and accumulate in the Congo deep-sea fan. In the recent lobe complex, large clusters of vesicomyid bivalves are found all along the active channel in areas of reduced sediment. These soft-sediment communities resemble those fuelled by chemoautotrophy in cold-seep settings. The aim of this study was to elucidate feeding strategies in these macrofaunal assemblages as part of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 125 publications
(167 reference statements)
1
20
0
Order By: Relevance
“…After this pioneer work, CSIA-FA has been extensively used to study nutritional pathways of chemosynthetic symbioses (Fang et al, 1993;MacAvoy, Macko, & Joye, 2002;Pruski et al, 2017;Streit, Bennett, Dover, & Coleman, 2015). After this pioneer work, CSIA-FA has been extensively used to study nutritional pathways of chemosynthetic symbioses (Fang et al, 1993;MacAvoy, Macko, & Joye, 2002;Pruski et al, 2017;Streit, Bennett, Dover, & Coleman, 2015).…”
Section: Compound-specific Isotope Analyses (Csia)mentioning
confidence: 99%
See 1 more Smart Citation
“…After this pioneer work, CSIA-FA has been extensively used to study nutritional pathways of chemosynthetic symbioses (Fang et al, 1993;MacAvoy, Macko, & Joye, 2002;Pruski et al, 2017;Streit, Bennett, Dover, & Coleman, 2015). After this pioneer work, CSIA-FA has been extensively used to study nutritional pathways of chemosynthetic symbioses (Fang et al, 1993;MacAvoy, Macko, & Joye, 2002;Pruski et al, 2017;Streit, Bennett, Dover, & Coleman, 2015).…”
Section: Compound-specific Isotope Analyses (Csia)mentioning
confidence: 99%
“…Data showed that fatty acid δ 13 C compositions were more negative (depleted) for the seep mussels (−56.9‰ to −49.0‰ against −34.4‰ to −24.9‰), which relied almost exclusively on endosymbiotic methanotrophic bacteria as a carbon source, than for coastal mussels, which had a mixed dietary intake from a large diversity of food sources. After this pioneer work, CSIA-FA has been extensively used to study nutritional pathways of chemosynthetic symbioses (Fang et al, 1993;MacAvoy, Macko, & Joye, 2002;Pruski et al, 2017;Streit, Bennett, Dover, & Coleman, 2015). For other symbiotic associations, FA-CSIA has proved to be particularly useful in elucidating dietary preferences of scleractinian corals.…”
Section: Compound-specific Isotope Analyses (Csia)mentioning
confidence: 99%
“…That C is remineralized, fixed once more into biomass through anaerobic oxidation of methane, and transferred to the macrofauna (Pruski et al . 2017). In this case the methane flux is also sufficient to sustain Vesicomyid bivalves and microbial mats, which did not occur at the site studied by the present authors (Pruski et al .…”
Section: Discussionmentioning
confidence: 99%
“…In this case the methane flux is also sufficient to sustain Vesicomyid bivalves and microbial mats, which did not occur at the site studied by the present authors (Pruski et al . 2017, Rabouille et al . 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation